CULTURAL-ECONOMIC AND HUMANITARIAN RELATIONS BETWEEN THE REPUBLIC OF SOUTH KOREA AND THE REPUBLIC OF UZBEKISTAN - Ergashev Islomjon (Journal Park Publishing, 2022)
This article discusses the cultural, economic and humanitarian relations between the Republic of Korea and the Republic of Uzbekistan.
Keywords: Relations; cooperation; states